*Kerh2- and *ker- Roots in Ancient Celtic Onomastics Against the Indo-European Background - Marcos Medrano Duque (Вопросы ономастики)
It is well known that the root *ker- ‘upper (body) part, horn’ and its secondary variant *kerh2- ‘head’ have enjoyed high productivity in all Indo-European languages, at least in the field of common names which was thoroughly surveyed in the past century by A. J. Nussbaum. However, these roots also left a large number of proper names in most western and southern daughter languages of PIE that on many occasions have not been satisfactorily identified or analysed to date. Such names have mainly been transmitted by the Roman epigraphic tradition, although some others can be found in Roman and Greek literary sources, so their phonetic structure may have been altered during the process of transmission. Therefore, the aim of this paper is to compile a comprehensive list of the onomastic traces of *kerh2- and *ker- roots in ancient and medieval Celtic languages and, where possible, in the rest of the Indo-European languages, paying special attention to the derivational and compositional processes, morphological structures, and dialectal trends deducible from the distribution and frequency of occurrence of proper names. Each proper name or group of proper names has been individually parsed and further cognates outside Celtic branch have been sought in order to seek common formational isoglosses. Last, other unresolved semantic and lexical issues concerning Celtic and Indo-European common derivatives of *ker- mainly found in the field of dendronymy (Greek κράνον/κράνεια ‘cornelian cherry’ and κέρασος ‘bird cherry’, Gaulish κόρνα, and Latin cornum/cornus ‘cornelian cherry’, etc.) will also be addressed at the end of the paper.